Integrasi Sains-Islam: Telaah Kritis Epistemologi Ziauddin Sardar dan Relevansinya bagi Perguruan Tinggi Keagamaan Islam Negeri Indonesia - Fian, Khafifatul; Mawardi, Kholid (Matan : Journal of Islam and Muslim Society, 2024)
Differences in views cause the need for scientific integration to create harmony. This is one of the efforts that need to be discussed and realized to minimize a dichotomy of science. This paper aims to analyze the integration of Islamic-science through a critical review of Ziauddin Sardar and its relevance in PTKIN. This paper includes the type of literature research with the acquisition of data collected through primary sources derived from Ziauddin Sardar's: "How Do You Know?: Reading Ziauddin Sardar on Islam, Science, and Cultural Relations" and a translated book by AE Priyono entitled " Jihad Intelektual: Merumuskan Parameter-Parameter Sains Islam", and supported by other sources with similar discussions. Data analysis is carried out based on the content and conclusions after the data is collected. The results showed that the purpose of Islamic-science is not to search for truth, but the Islamic ethos based on the Qur'an is used as a reference in science research and is also based on the will of the Muslim community. Sardar's principles of Islamization include Islam should be seen as an ethical framework rather than a state, the Qur'an should be viewed as an interpretive methodology to deal with contemporary issues, and Muslims should be active truth seekers rather than passive. The development of various PTKIN in the current era based on science integration shows that there is relevance or no rejection of the concept of Islamization of science.